Synthesis and characterization of [BaO-(10-x)ZrO2-TiO2-SiO2-xCrO3] type glass and glass ceramics. Issue 4 (1st October 2020) - Fatima, Zaireen; Ajaz, Hussain; Gautam, Chandkiram; Shweta; Singh, Prakash; Ahmed, Afroz; Singh, Gulab; Singh, Manoj Kumar
ABSTRACT: Various glass compositions were prepared in a glassy system [25BaCO3 -(10- x ) ZrO2 -20TiO2 -45SiO2 - x CrO3 ] ( x = 0, 2, 4, and 6) using melt-quenching technique. XRD patterns of glass and glass ceramics showed amorphous and crystalline nature. Density of glass and glass ceramics decreased from 3.4553 to 3.4381 g/cm 3 and 3.7485 to 3.1977 g/cm 3 with increasing concentration of CrO3 . DTA of the glasses revealed a shift in base line which suggests a change in specific heat and attributed to the glass transition temperature, Tg . FTIR and Raman spectroscopic analysis indicated that an increasing doping of CrO3 changes structural network by increasing number of nonbridging oxygens (NBO) within glassy matrix. These results revealed that bands toward low frequency side endorsed to the vibration of Ba 2+ metal cation, bending vibration of Si-O-Si and bonding formation of ZrO2 . Concentration of CrO3, changed the microsture significantly and hence, a denser, fully developed mixed morphology was noticed with spherical grains of ZrO2, irregular shape of bazirite (BaZr0.97 Ti0.03 Si3 O9 ) phase and TiO2 grains. Glass ceramic sample BZTS6C971 CrO3 ( x = 6) retains high value of dielectric constant, ~4555 due to space charge polarization. Hence, these glass ceramics might be useful for diverse applications such as in optical devices, electronic circuits, and multilayer ceramic capacitors.